Avocado dessert sebagai Makanan Tambahan untuk Cegah Stunting di Aceh Tengah - Andini, Mirna Ria (Apik Cahaya Ilmu, 2024)
Stunting is a condition in which a child's growth and development are stunted due to chronic malnutrition, inadequate care, and poor living conditions, usually occurring in the early years of life, especially before the age of five. Stunting is often characterized by low height for a given age, indicating that the child's height is well below the average height for his or her age group. What more in developing countries, for example Indonesia itself. There are several areas that have stunting problems that are very easy to find, for example in Central Aceh. Aceh Tengah has a fairly high stunting ranking in several regions. Nutrition is a factor that we need to take care of because nutrition has an important role for our bodies and the optimal growth and development of children. Avocados contain nutrients and unsaturated fats that are good for babies, which are needed to support their brain and body development. Avocados are high in nutrients for babies such as vitamins and minerals. Some of these include vitamins C, A, K, E, and B6, as well as folate, thiamin, calcium, iron, potassium, and sodium. Avocado Utilization as PMT in Stunting Prevention Efforts in Segene Balik Village. The method used in this service is the socialization method by distributing brochures introducing one of the avocado preparations that can be useful for preventing stunting, namely avocado dessert. The results of this activity are that the cadre women are able to process avocados to prevent stunting in Segene Balik Village